Řízení 3 os modelu manipulátoru - Matějíček, Miroslav (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2010)
Bakalářská práce se zabývá řízením 3 os modelu manipulátoru pomocí servopohonů za pomoci instrumentace firmy Allen Bradley. Použito je PLC řady ControlLogix, které řídí servopohony pomocí rozhraní SERCOS a řídící částí Kinetix 2000. V práci je uveden postup konfigurace os i konfigurace koordinovaného systému a způsob programování řízení os včetně ukázkové laboratorní úlohy.

Bachelor thesis deals with controlling of free axes of manipulator model by the help of servo – actuator with the help of instrumentation from the company Allen Bradley. It is used PLC from the series ControlLogix, which controls servo – actuators with the help of interface SERCOS and the control part Kinetix 2000. The procedure of the configuration of axes and configuration of coordinated system and a method of programming of the governing of axes including an exemplary laboratory work are given in the thesis.
Control of three axis of manipulator
Keywords: PLC; řízení; SERCOS; Kinetix; PLC; Control; SERCOS; Kinetix